A phenomenological observation of two theatrical learning environments - Freeby, Raymond (Kansas State University, 2013)
This modified qualitative study focused on observations of learning procedures and performance outcomes of two theatrical learning environments (TLE), using a select set of phenomenological observation and recording procedures to ensure minimization of researcher bias. Observational results were compared to previously published observations of a large lecture hall learning environment at a Midwestern university. Observational results were also compared to a select set of learning theories to determine similarities in observed learning procedures to those theories. This study reveals differences in methods of acquisition of knowledge and skills in a TLE and the acquisition of same in the lecture hall environment. In the large lecture hall descriptions, the individual learner’s preset learning measurement options of ABCDF or Pass/Fail, individual option of choice to be present but non-interactive within the learning environment, individual option of choice of when to learn material and in what manner (for instance, cramming for a final), option of choice of attention level when physically present in the learning environment, and other options all affect the individual learner’s achievement level while minimally impacting the learning and achievement options of other members of the lecture class. This contrasts with a TLE, where failure is not a pre-listed option, maximization of learning and skills development is a constant goal individually and severally, interactivity with other learning environment members is mandated, material must be progressively learned and mastered by all members at essentially the same rate of progress, attention level must remain high, and there may well be multiple ‘final exams’ wherein virtually 100% of text materials must be transmitted verbatim in a meaningful way to a third party (an audience) through skills learned. Comparisons of learning theories reveal this process to be most closely allied with, but still significantly different from, collaborative learning theory.
Keywords: Education; Education, General (0515)